Kebakaran gedung terra drone : analisis hukum pidana atas pelanggaran standar keselamatan bangunan - Akhmad, Irkham (Maliki Interdisciplinary Journal, 2026)
Building fires are events that not only cause material losses but also threaten public safety, thus having complex legal dimensions. In law enforcement practice in Indonesia, building fires are often positioned as administrative or civil matters, while the aspect of criminal liability has not been optimally examined. This study aims to analyze the Terra Drone building fire from a criminal law perspective, particularly in relation to violations of building safety standards and the possibility of criminal liability arising from them. The research method used is normative juridical with a legislative, conceptual, and case approach, supported by a literature study of primary, secondary, and tertiary legal materials. The results of the study show that violations of building safety standards cannot always be viewed as mere administrative violations. Under certain conditions, these violations can constitute criminal acts, especially if there is evidence of negligence that endangers public safety. This study also confirms the potential for corporate criminal liability if a fire is the result of a policy or systematic negligence by the building manager. Thus, criminal law has a strategic role in providing protection for public safety while encouraging compliance with building safety standards.